Zinc Biofortified Rice Varieties-Impact in Human Health - Suman, K.; Keerthi, I.; Jaldhani, V.; Sundaram, R. M.; Neeraja, C. N. (Chronicle of Bioresource Management, 2025)
Rice is one of the commonly consumed staple foods across the world and more than 50% of the calorific needs are met by rice for most of the population in many Asian countries. Most of the modern high-yielding rice varieties are reported to be poor in nutrient content after polishing especially zinc (13-16 ppm). Biofortification is the process of increasing the density of vitamins and minerals in a crop through various approaches can help in tackling hidden hunger. More than two billion people across the world, mostly children and pregnant and lactating women suffer zinc deficiency. To overcome malnutrition especially zinc, iron and protein, ICAR initiated a national level research programme on Biofortification across various crops with Indian Institute of Rice Research (ICAR-IIRR) as main coordinated centres in collaboration with other national research institutes in India. ICAR-IIRR tested the nominated biofortified rice entries with high yield in the national wide research zones from 2013 through IIRR-AICRIP Biofortification programme. Since 2015, four popular zinc biofortified (>24 ppm in polished rice) rice varieties released by ICAR-IIRR. These varieties could play a significant role in combating malnutrition where rice is a major staple food.